Technical Efficiency of Wheat Production in the Gezira Scheme - Al-Feel, Mohamed Ahmed; Fadel Mola, El Moez Abdel Allah (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was carried out to measure the technical efficiency of wheat production in the Gezira scheme and to determine the most important socio-economic factors affecting this efficiency, using the stochastic production frontier model. Primary and secondary data were used. The former were collected from a random sample of 100 farmers from Waddel Mansi sector of the Gezira scheme, while the latter were collected from relevant sources. The results showed that the mean technical efficiency was 0.73, which means that the scheme produced 73% of the possible wheat production at the current levels of production inputs and technology. In other words, wheat production could have been increased by 27%, at the same levels of inputs had farmers been technically efficient. The results also showed that 97% of wheat output deviations from normal were caused by differences in farmers' levels of technical efficiencies and were not due to the out of control random nature of the agricultural production. Wheat area, sowing date, degree of infection with pests and diseases, number of insufficient irrigations and farmers' experience appeared to be the most important factors determining wheat output in the Gezira scheme. The off-farm income appeared to have negative effects on wheat production, because of its timing contradictions with some important agricultural operations. The farmers' gender, land tenure, land preparation, marital status and farm location with respect to the irrigation canal, represented the most important socio-economic factors determining farmers' efficiencies of wheat production in the Gezira scheme.